Violent Conflict and the Road Sector : Points of Interaction - Rebosio, Michelle; Wam, Per Egil (World Bank, Washington, DC, 2013)
Roads are vital in the stabilization and reconstruction of a conflict-affected country. These initiatives impact population groups and their relationship with one-another through infrastructure construction and maintenance, through processes of decision-making and participation, and most significantly through their outcomes. The impacts of roads sector initiatives are felt by large sections of the population and can have effects not only on those directly benefitting from the project but on economic growth, resource distribution, governance, and security. These wide-ranging effects can in turn impact conflict and a country's prospects for stability and resilience. This note is organized in the following way: section one presents the methodology of the study, including the selection of cases and sources of information. Section two presents the conflict context, including a description of some of the main characteristics of these contexts that could have profound implications for development initiatives. Section three discusses the tradeoffs that those working in the roads sector usually need to make in a conflict context. Section four looks at key areas of interaction between the roads sector and conflict, focusing on questions that need to be asked during design and implementation and regarding potential effects of roads sector projects on conflict. Finally, the author concludes with some recommendations for those working on the roads sector in transport settings.